Artisanal Fisher Association Leaders’ Estimates of Poaching in Their Exclusive Access Management Areas - Romero, Pedro; Estévez, Rodrigo A.; Romero, Pablo; Gelcich, Stefan (Frontiers in Marine Science, 2022)
In marine environments, poaching can become a key threat to marine ecosystem conservation. Poaching can occur in marine protected areas and/or in fishery management areas. Unfortunately, understanding the magnitude and characteristics of poaching under community based and co-management governance schemes in coastal and marine environments, has not received the attention it deserves. In Chile, a system of Territorial Users Rights for Fisheries (TURF) has been recognized as one of the largest experiences of small-scale fisheries co-management at a global scale. Currently, poaching is one of the main threats to the TURF system in Chile. In this article, we assessed poaching of a highly valuable benthic resource (Concholepas concholepas) from TURF management areas. We estimated artisanal fisher association leaders’ perceptions of poaching within their TURFs and explore determinants of poaching for Concholepas concholepas. Poaching of Concholepas concholepas showed differences along the studied sites. As expected, the greater abundance of Concholepas concholepas in the management areas generates an increased incentive to poach. Areas that make the greatest investment in surveillance are those most affected by poaching. However, our study cannot determine the effectiveness of current levels of surveillance on illegal extraction. Results show older areas tend to reduce the levels of illegal extraction, which could indicate a greater capacity and experience to control poaching. Supporting fisher associations in enforcing TURFs and following up on sanctions against perpetrators are conditioning factors, highlighted by fisher leaders, for TURF sustainability. The approach used in this study provides insights to prioritize geographies and opportunities to address poaching in small-scale co-managed fisheries.